(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study aims to analyze the role of English language in the digital economy, focusing on its significance in IT, Fintech, and online economic platforms. The objective is to investigate how English proficiency influences professional communication, technical knowledge acquisition, and participation in global digital markets. The research employs a mixed-methods approach, combining qualitative analysis of digital platform content and quantitative surveys among IT and Fintech professionals. Data were collected from online learning resources, global platforms such as GitHub, Upwork, and digital financial services, and through questionnaires targeting university students and industry specialists. The findings indicate that English is essential for understanding technical documentation, coding languages, Fintech operations, and global online business transactions. Proficiency in English directly correlates with the ability to access advanced technological tools, participate in international collaborations, and enhance employability in the digital economy. This study contributes to digital economy literature by linking language competence with economic participation. It emphasizes the communicative function of English as a key enabler of knowledge transfer, innovation adoption, and cross-border business in the context of digital transformation. Implications for Practitioners/Policy: The study highlights the necessity of integrating English language training into IT and Fintech education. Policymakers and academic institutions should develop programs that combine language skills with technical competencies to prepare students and professionals for the global digital market. The research focuses primarily on English in digital economy contexts and may not fully capture regional language variations or multilingual platforms. Future studies could extend this research by exploring comparative impacts of multiple languages on digital economic participation